Tilt table testing to diagnose pseudosyncope in the pediatric population. (27th February 2017) - Robinson, Jeffrey A.; Shivapour, Jill K.; Snyder, Christopher S.
Abstract: Objective: Pseudosyncope can be difficult to distinguish from true syncope. Often, pediatric patients with pseudosyncope undergo multiple tests and referrals before the appropriate diagnosis is reached. The purpose is to describe the utility of the head‐up tilt table test to elicit the diagnosis of pseudosyncope in the pediatric population. Design: Retrospective chart review from November 2012 to December 2015 of patients age ≤23 years referred for 30‐minute, 80‐degree tilt table test. Pretest probability for pseudosyncope was high if there was no response to traditional management, atypical episodes, occurrence during undesirable exercise, or prolonged episode duration. Inductive techniques were utilized to persuade patients of the likelihood of experiencing an episode during the procedure. Pseudosyncope was confirmed when a patient had normal vital signs during their event and had reflex responses to disruptive maneuvers. Results: Tilt table testing was performed on 89 patients [median age 16 years (5–23); 26% male] with the majority (60%) being negative for pseudosyncope, including 51 true negatives and 2 false‐negatives. Of the 36 patients with syncope during tilt table testing, 28 were diagnosed with vasovagal syncope and 8 with pseudosyncope [median age 16 years (15–21); 38% male]. Pseudosyncope episodes were observed immediately in 2 patients. All patients with late‐onset pseudosyncope required inductive techniques prior to the recorded episode. Conclusions: Pseudosyncope can be identified during tilt table testing if inductive techniques are utilized in patients with a high index of suspicion. Disruptive maneuvers are excellent adjunctive methods to confirm the diagnosis. Tilt table testing is an effective means to identify pseudosyncope and allow appropriate diagnosis and treatment.